(untitled) (REMUNOM, 2025)
This article analyzes the challenges of distance education in the face of the need for active methodologies, focusing on the perspective of anti-racist education applied to the Judiciary of Pernambuco. The research used an online questionnaire as a methodological instrument, addressing the perception of employees regarding inclusive practices and racial equity policies. The results indicate low participation in anti-racist training, a widespread perception of insufficient institutional actions, and a strong demand for structural policies that promote diversity and inclusion. Anti-racist education, articulated with active methodologies, proves essential for promoting a more just and equitable environment, with a direct impact on professional practice and the administration of justice.